Heating properties of bridge decks using hydronic heating systems with internal or external circulation tubes - Xin Chen; Gang qiang Kong; Han long Liu; Qiang Jiang (Energy and Built Environment, 2023)
A comparison analysis of the heating properties of the hydronic heating system of bridge decks with external (exchange tubes installed at the bottom of the existing bridge deck with voids inside) or internal (exchange tubes embedded in pavement of the newly built bridge deck) tubes was carried out through field tests. Two heating methods (constant heating power and constant inlet fluid temperature) were used to analyze the heat exchange flux and the temperature increments as well as thermally induced stress of the slab. Numerical simulation was conducted to model the bridge deck heating process to analyze the temperature distribution of the bridge surface. The results shows that the heat exchange flux are the same under the same constant heating powers for the two embedded tube position heating systems; the maximum temperature increment of the bridge deck surface obtained by the external heating system is 0.46 times that obtained by the internal heating system; the maximum thermally induced stress caused by the external heating is 20.4% of the concrete strength (19.1 MPa), which is much higher than that caused by the internal heating under the same heating powers. The thermal efficiencies of the external and internal heating systems are approximately 24.4% and 47.9%, respectively. Under the same constant inlet temperatures, the temperature increment of the bridge deck caused by the external heating is 20.4% of that of the internal heating.